2021
DOI: 10.3389/fmolb.2021.755577
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fucose-Containing Glycan Motifs Across Taxonomic Kingdoms

Abstract: The extraordinary diversity of glycans leads to large differences in the glycomes of different kingdoms of life. Yet, while most monosaccharides are solely found in certain taxonomic groups, there is a small set of monosaccharides with widespread distribution across nearly all domains of life. These general monosaccharides are particularly relevant for glycan motifs, as they can readily be used by commensals and pathogens to mimic host glycans or hijack existing glycan recognition systems. Among these, the mon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…This observation supports previous accounts of low levels of fucosylation in invertebrate O -glycans. 64 The presence of methylation in both the N- and O -glycans supports prior reports on both marine and land snails, and identified compositions are similar to those identified in other snails. 65 A difference is the degree of methylation, as previous studies on other species reported high levels (3 – 4 methyl groups per monosaccharide), while our studies indicate lower levels of methylation (0 – 2 methyl groups).…”
Section: Resultssupporting
confidence: 85%
“…This observation supports previous accounts of low levels of fucosylation in invertebrate O -glycans. 64 The presence of methylation in both the N- and O -glycans supports prior reports on both marine and land snails, and identified compositions are similar to those identified in other snails. 65 A difference is the degree of methylation, as previous studies on other species reported high levels (3 – 4 methyl groups per monosaccharide), while our studies indicate lower levels of methylation (0 – 2 methyl groups).…”
Section: Resultssupporting
confidence: 85%
“…In glycobiology, deep learning has recently enabled new analyses of sequence–function relationships. [ 17 , 18 ] Based on this, we developed SweetNet, [ 8 ] a graph convolutional neural network method that learns glycan representations by taking their branching structures into account. Briefly, SweetNet considers glycans as molecular graphs, with monosaccharides and linkages as nodes.…”
Section: Introductionmentioning
confidence: 99%
“…Next to being used for downstream models that can use these similarities as new features for prediction, learned glycan similarities can be used to visualize clusters of related glycans, for instance via t-SNE or UMAP mentioned above, and allow for interpretation of learned glycan associations. In a recent study, this has been for instance used for an in-depth investigation of the role and properties of different fucose-containing motifs across taxonomic kingdoms …”
Section: Next-generation Machine Learningmentioning
confidence: 99%
“…In a recent study, this has been for instance used for an in-depth investigation of the role and properties of different fucose-containing motifs across taxonomic kingdoms. 127…”
Section: Deep Learning and Glycobiologymentioning
confidence: 99%